Indigenous Knowledge and Poverty Alleviation in Contemporary Zimbabwe - Tasara Muguti; Theresa Zibengwa (Springer, Singapore, 2022)
The study seeks to unpack the extent to which indigenous knowledge can be used in the fight against poverty among Zimbabwean rural communities. Across the globe, poverty remains a huge challenge with extreme poverty confined mostly to rural communities in developing countries. Today, Zimbabwe has disintegrated into one of the poorest countries in Africa with alarming poverty levels. Poverty among the ordinary citizens has been exacerbated by the multi-layered challenges facing the country. While various scientific interventions have been embraced in Zimbabwe to mitigate poverty among rural communities, its levels remain alarmingly high. The study believes that scientific interventions alone can no longer be relied upon to deal with contemporary challenges. Thus, there is need for a critical evaluation of the indigenous juxtaposed with the foreign, for modern societies to forge ahead with realistic and pragmatic development.